A prática pedagógica e a liberdade sartriana na educação de jovens e adultos da Escola Estadual Marechal Rondon, Araguaína-TO - Santos Sobrinho, Lucymara da Silva (Universidade Federal do Tocantins, 2023)
This study proposes a didactic sequence for students of Youth and Adult Education (EJA) at Escola Marechal Rondon in the Araguaína-TO, highlighting the theme “freedom” for the philosopher Sartre. The activities were carried out remotely with the students, due to the need for social distance imposed by the COVID-19 pandemic. The students received various materials with contents on the philosophical concept of “Sartre’s Freedom”, creating an environment for debate in the classroom, where students could reflect and incorporate the concept of freedom in Sartre into their lives. Thus, the teaching of Philosophy at EJA, with Sartre's theme, contributes to the formation of young people and adults, taking them out of alienation, which is reflected in the way they see their freedom, their own choices, and responsibilities, making them aware of their place in the world.